2004
DOI: 10.1074/jbc.m409430200
|View full text |Cite
|
Sign up to set email alerts
|

Ectodomain Shedding and Intramembrane Cleavage of Mammalian Notch Proteins Are Not Regulated through Oligomerization

Abstract: Intramembrane cleaving proteases such as site 2 protease, ␥-secretase, and signal peptide peptidase hydrolyze peptide bonds within the transmembrane domain (TMD) of signaling molecules such as SREBP, Notch, and HLA-E, respectively. All three enzymes require a prior cleavage at the juxtamembrane region by another protease. It has been proposed that removing the extracellular domain allows dissociation of substrate TMD, held together by the extracellular domain or loop. Using ␥-secretase as a model intramembrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
78
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 73 publications
7
78
1
Order By: Relevance
“…Annexin-V flow cytometry ( Figure 6c) indicated that cytotoxicity was at least in part due to apoptosis. Either Notch-1 or IKKa siRNAs dramatically inhibited both NF-kB and CBF-1 reporter activity in the presence or absence of 10 mM cisplatin (Figures 6d and e), consistent with the hypothesis that NF-kB and CBF-1 activities are (Vooijs et al, 2004). Forty-eight hours after transfection, cells were treated for 30 min with vehicle or TNF-a (10 ng/ml).…”
Section: Notch-1 Maintains Nf-kb Activity In Caski Cellssupporting
confidence: 65%
See 1 more Smart Citation
“…Annexin-V flow cytometry ( Figure 6c) indicated that cytotoxicity was at least in part due to apoptosis. Either Notch-1 or IKKa siRNAs dramatically inhibited both NF-kB and CBF-1 reporter activity in the presence or absence of 10 mM cisplatin (Figures 6d and e), consistent with the hypothesis that NF-kB and CBF-1 activities are (Vooijs et al, 2004). Forty-eight hours after transfection, cells were treated for 30 min with vehicle or TNF-a (10 ng/ml).…”
Section: Notch-1 Maintains Nf-kb Activity In Caski Cellssupporting
confidence: 65%
“…Both direct and reverse immunoprecipitation experiments detected a Notch-1/IKKa-containing complex in normal keratinocytes as well (Figure 3e), indicating that this complex is not exclusive to CaSki and T-ALL cell lines. To confirm the interaction, we used a quantitative immunoprecipitation assay described by Vooijs et al (2004). This assay uses a full-length Notch-1 construct tagged at the C terminus with Renilla luciferase.…”
Section: Notch-1 Maintains Nf-kb Activity In Caski Cellsmentioning
confidence: 99%
“…Similar to APP, numerous other γ-secretase substrates dimerize via their TMS, e.g., E-cadherin (23), ErbB4 (24), or Notch (25), and it is reasonable to speculate that certain GSMs may similarly modulate processing of those substrates. Indeed, sulindac sulfide and indomethacin decreased the relative level of released Notch-1 Aβ-like peptide species, i.e., Nβ25, without changing the total Nβ level (26).…”
Section: Discussionmentioning
confidence: 99%
“…Models involving receptor oligomerization have been proposed, but recent data suggest that both metalloprotease-sensitive and -resistant forms of NOTCH receptors exist primarily as monomers (46). An alternative mechanism supposes that NOTCH1 is rendered sensitive to S2 cleavage by a change in conformation (46), which could occur in response to mechanical forces generated by the endocytic machinery of the ligand-expressing cell (1,22,30,43).…”
mentioning
confidence: 99%